Degradation and Reorientation of the Living Guidelines of the Indigenous Dayak Peoples of West Kalimantan - Salfius Seko; Alfonsus Hendri Soa; Lolita Lolita (International Journal Ethnic, Racial and Cultural Heritage, 2023)
Indigenous philosophy is the basis for customary law communities in building their community life. In order for the life of the community to run well, a value system is created to guide life that originates from religious, social, and cultural life in relation to the supernatural between humans and nature. The value system that guides the life of the indigenous Dayak community is experiencing a process of degradation. The basic and urgent problem lies in life teaching in the form of advice, advice which is summarized in traditional saying which is no longer an important teaching in society and in the family because of the influence of modernization and social institutions. It is necessary to reorient the system of values and institutions by teaching traditional proverbs. This study uses empirical legal research methods to collect data as material for research conducted, the results of data collection in the field show that proverbs are spoken languages that are often used by the Dayak community in various activities in the Dayak community, for example in traditional ceremonies, traditional meetings, customary dispute resolution, traditional marriages,  giving advice to children and so on. The forms of proverbs used depend on the activities carried out by the community, for customary deliberation activities, customary dispute resolution, traditional marriages are in the form of sayings and sayings, while for teaching and advice to children are in the form of proverbs and parables.